Assessing the relationship between community engagement and perceived ownership of an urban park in Philadelphia. (27th May 2019) - Mullenbach, Lauren E.; Baker, Birgitta L.; Benfield, Jacob; Hickerson, Benjamin; Mowen, Andrew J.
Abstract: Urban parks provide many benefits, though evidence of environmental injustice associated with certain park investments is growing. Some cities fail to engage communities in park planning, which can reduce residents' sense of ownership of new and renovated parks and disconnect them from the neighborhood social fabric. Thus, this study assessed the outcomes of resident engagement with an urban park nonprofit located in a low-income community of color in Philadelphia. We developed new metrics measuring perceived engagement with park planning and programming and its association with perceived community ownership and perceptions of the park as part of the neighborhood social fabric. We analyzed these variables following a renovation using confirmatory factor analysis and structural equation modeling. Results showed significant relationships between perceived community engagement and perceptions of the park as a community asset. These findings underscore the importance of engaging communities in park planning to enhance ownership and avoid feeling excluded.